Anti-Fibrotic Activity of an Antimicrobial Peptide in a Drosophila Model. - Khalili, D.; Kalcher, C.; Baumgartner, S.; Theopold, U. (Journal of innate immunity, 2021)
Fibrotic lesions accompany several pathological conditions, including tumors. We show that expression of a dominant-active form of the Ras oncogene in Drosophila salivary glands (SGs) leads to redistribution of components of the basement membrane (BM) and fibrotic lesions. Similar to several types of mammalian fibrosis, the disturbed BM attracts clot components, including insect transglutaminase and phenoloxidase. SG epithelial cells show reduced apicobasal polarity accompanied by a loss of secretory activity. Both the fibrotic lesions and the reduced cell polarity are alleviated by ectopic expression of the antimicrobial peptide drosomycin (Drs), which also restores the secretory activity of the SGs. In addition to extracellular matrix components, both Drs and F-actin localize to fibrotic lesions.